2001
DOI: 10.1037/0033-295x.108.4.814
|View full text |Cite
|
Sign up to set email alerts
|

The emotional dog and its rational tail: A social intuitionist approach to moral judgment.

Abstract: Research on moral judgment has been dominated by rationalist models, in which moral judgment is thought to be caused by moral reasoning. Four reasons are given for considering the hypothesis that moral reasoning does not cause moral judgment; rather, moral reasoning is usually a post-hoc construction, generated after a judgment has been reached. The social intuitionist model is presented as an alternative to rationalist models. The model is a social model in that it de-emphasizes the private reasoning done by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

92
2,499
7
129

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 5,743 publications
(2,938 citation statements)
references
References 147 publications
92
2,499
7
129
Order By: Relevance
“…Research emphasizing the importance of impulses in motivating other-regarding behavior (de Waal, 1997(de Waal, , 2006Haidt, 2001;Haidt & Kesebir, 2010) Kogut & Ritov, 2005;Pillutla & Chen, 1999). Our manipulation of salience of interpersonal impact is similar to those used in this past work.…”
Section: Theoretical Implicationsmentioning
confidence: 80%
See 1 more Smart Citation
“…Research emphasizing the importance of impulses in motivating other-regarding behavior (de Waal, 1997(de Waal, , 2006Haidt, 2001;Haidt & Kesebir, 2010) Kogut & Ritov, 2005;Pillutla & Chen, 1999). Our manipulation of salience of interpersonal impact is similar to those used in this past work.…”
Section: Theoretical Implicationsmentioning
confidence: 80%
“…One set of findings (e.g., Gino et al, 2011;Mead et al, 2009) suggested people are tempted by impulses to behave in a self-serving manner and use cognitive control, the ability to override such impulses, as "the moral muscle" (Baumeister & Exline, 1999, p. 1165, or COGNITIVE CONTROL AND SOCIALLY DESIRABLE BEHAVIOR 27 the motivator of socially desirable behavior. Another set of findings (e.g., Cornelissen et al, 2011;Zhong, 2011) suggested that an important role in motivating socially desirable behavior belongs to more primitive parts of human psychological machinery, guiding socially desirable behavior through impulses (de Waal, 2006;Haidt, 2001). This research proposed that people experience other-regarding impulses and that cognitive control can be used to override such impulses, allowing people to engage in more self-serving behavior (Cornelissen et al, 2011;Zhong, 2011).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Furthermore, it can explain why foreign language reduces confidence in one's moral evaluations (Geipel et al, 2015b). The strong aversive reaction that promotes moral condemnation (e.g., Haidt, 2001) might be the same that inspires confidence in one's judgment. Further supporting evidence comes from other domains.…”
Section: Why Does Foreign Language Sway Moral Judgments?mentioning
confidence: 99%
“…A critique that might be raised is that researchers mostly study moral psychology by analyzing subjects' explicit verbal reports of their reasoning while many moral psychologists now hold that moral behavior and moral judgment do not correlate with explicit reasoning (e.g., Haidt 2001;interestingly, Piaget [1932] was already aware of this difficulty). On the other hand, explicit verbal reasoning is used to convince others about one's moral judgments and to influence others' moral behavior (also Haidt 2001).…”
Section: Moral Heuristicsmentioning
confidence: 99%
“…On the other hand, explicit verbal reasoning is used to convince others about one's moral judgments and to influence others' moral behavior (also Haidt 2001). This suggests that it is appropriate to approach the issue of folk morality from different angles: moral behavior, implicit moral judgments, and explicit moral reasoning.…”
Section: Moral Heuristicsmentioning
confidence: 99%